Nile sparrows - Aṣlān, Ibrāhīm (Modern Arabic writing., 2004)
Set in the author's own Nile-side neighborhood of Warraq, Aslan's second novel, the first to be translated and published in English, chronicles the daily rhythm of life of rural migrants to Cairo and their complex webs of familial and neighborly relations over half a century. It opens with the mysterious disappearance of the tiny grandmother, Hanem, who is over 100 years old and is last seen by her daughter-in-law Dalal. Dalal does not have the heart to tell Hanem that her grown children Nargis and Abdel Reheem have both been dead for some time. Her grandson Mr. Abdalla, who has children of hi.